PENGARUH KONSENTRASI SUKROSA TERHADAP KARAKTERISTIK SARI BUAH PROBIOTIK TERONG BELANDA (Solanum betaceaum Cav.) TERFERMENTASI DENGAN ISOLAT Lactobacillus sp. F213 - Agung Prawitasari, Ida Ayu; Nocianitri, Komang Ayu; Kencana Putra, I Nengah (Jurnal Ilmu dan Teknologi Pangan (ITEPA), 2020)
This research was aimed to determine the effect of sucrose on the characteristics of tamarillo probiotic juice which was fermented by Lactobacillus sp. F213 and to determine the concentration of sucrose that produced the best characteristic of fermented tamarillo probiotic juice. This research used random block design with concentration of sucrose as treatments, which consisted of five levels: 0%, 3%, 6%, 9%, and 12%. Treatment was repeated 3 times to obtain 15 units of sample. Data were analyzed by analysis of variance followed by multiple comparison test of Duncan Multiple Range Test (DMRT). The result showed that different concentration of sucrose significantly affected total lactic acid bacteria (LAB), total sugar, total acid, pH, color (score), flavor (hedonic), sour taste (score), sweet taste (score), overall acceptance (hedonic), but had no significant effect on color (hedonic) and aroma (hedonic). The 9% sucrose treatment produced the best fermented tamarillo probiotic juice with the characteristics of 9.31 log CFU/mL total LAB, 16.98% total sugar, 1.53% total acid, pH of 4,31, orange color, with slightly sour and sweet taste, aroma, and overall acceptance liked slightly.